2018
DOI: 10.1007/s10973-018-7238-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyethyl methyl cellulose as a modifier of gypsum properties

Abstract: The study is focused on the influence of a water-soluble polymer (in weight fraction up to 1.5%), cellulose derivativeshydroxyethyl methyl cellulose, on gypsum properties. Gypsum setting involves two processes: gypsum hydration/crystallization and probably formation of a polymer film in material pores. The processes are studied by various methods such as setting time and mechanical measurements, scanning electron microscopy and differential scanning calorimetry. The additive acts as a retarder (an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The main goal of using polymers in gypsum slurry is the modification of setting process, which involves gypsum hydration/crystallization and final structure of gypsum matrix [4]. Based on the application in cements, Pouches revealed that polymers had the considerable influence on hydration delay [5].…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of using polymers in gypsum slurry is the modification of setting process, which involves gypsum hydration/crystallization and final structure of gypsum matrix [4]. Based on the application in cements, Pouches revealed that polymers had the considerable influence on hydration delay [5].…”
Section: Introductionmentioning
confidence: 99%
“…Certain information is available on the effect of water-soluble polymers on the microstructural formation of cementitious materials [1][2][3]. During the hydration of calcium sulfate hemihydrate, calcium sulfate dihydrate (gypsum plaster) is formed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous results also proved the influence of other watersoluble polymers on the setting induction time, the rate of hydration as well as certain mechanical and thermal properties of the final product. The cellulose derivatives are found to be suitable retardant additives for the modification of gypsum setting [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…Gypsum has low plastic resistance and may suffer fractures when subjected to the tractive effort because of its covalent and ionic bonds, which give greater force and proximity to the molecules. Many studies [1][2][3][4][5] have been made using gypsum-based composite materials (GBCM) with polymers with the goal of enhancing its performance. The polymeric materials have extensive chains composed of repetitions of units that are joined by weak Van der Waals bonds 6,7 , giving greater flexibility than the ceramic materials.…”
Section: Introductionmentioning
confidence: 99%